HARMONI DI PASURUAN: TITIK TEMU ULAMA SYIAH DENGAN ULAMA PESANTREN - Makhfud Syawaludin (Journal Multicultural of Islamic Education, 2023)
The potential for conflict and harmony in Pasuruan have the same opportunity to develop, it's just a matter of caring for and developing the potential for harmony or allowing conflict to occur. The research method used during research in Pasuruan Regency used a qualitative method with a phenomenological approach. The methods for collecting data are unstructured and open interviews, moderate participant observation, and documentation. Next, data analysis and interpretation were carried out according to Miles and Huberman (1984) using the following steps: a). Data reduction, b). Display data, and c). Conclusion drawing/verification. There are four meeting points between Shia Ulama and Islamic Boarding School Ulama in Pasuruan. First. Viewing and solidarity in various Islamic teachings and organizations. Second. Rejecting the misdirection of various Islamic teachings and organizations. Third. Seeing similarities with Sunni-Shia dialogue. Fourth. Support the Republic of Indonesia and be open in choosing the country's leader.